2016
DOI: 10.1111/hiv.12397
|View full text |Cite
|
Sign up to set email alerts
|

HIV viraemia and mother‐to‐child transmission risk after antiretroviral therapy initiation in pregnancy in Cape Town, South Africa

Abstract: High rates of VS at delivery and low rates of MTCT can be achieved in a routine care setting in sub-Saharan Africa, indicating the effectiveness of currently recommended ART regimens. Women initiating ART late in pregnancy and with high VL appear substantially less likely to achieve VS and require targeted research and programmatic attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 19 publications
6
87
0
2
Order By: Relevance
“…To our knowledge, only one other study has reported on VL outcomes of a PMTCTB+ cohort in sub-Saharan Africa and reported similar findings [37]. VL monitoring was still quite a novel practice for health workers and its routine use for treatment monitoring was still not fully established [38].…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, only one other study has reported on VL outcomes of a PMTCTB+ cohort in sub-Saharan Africa and reported similar findings [37]. VL monitoring was still quite a novel practice for health workers and its routine use for treatment monitoring was still not fully established [38].…”
Section: Discussionmentioning
confidence: 90%
“…17 In a study of over 1000 women starting Option B+ in public clinics in Malawi, 81% of women tested had HIV RNA <1000 copies/ml at 6 months after ART initiation, but 35% of women had no viral load testing performed. In a cohort of women who initiated ART during pregnancy in a study at a public clinic in Cape Town, South Africa in which viral loads were assessed routinely, 91% achieved viral suppression to <1000 copies/ml by delivery, 18 but only 70% maintained viral suppression to 12 month postpartum. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Women experiencing acute HIV infection, especially late in pregnancy and/or during the breastfeeding period, are most likely to transmit infection to their babies (3). Even when mothers are diagnosed with HIV and started on ART during the breastfeeding period, the risk of MTCT remains high due to poor maternal adherence (4)(5)(6). Thus, in 2015, ϳ150,000 infants (ϳ400 infants per day) became newly infected with HIV, half by breastfeeding (7,8).…”
mentioning
confidence: 99%